1985
DOI: 10.1111/j.1365-2362.1985.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

B complex vitamins activate rat guanylate cyclase and increase cyclic GMP levels

Abstract: Since B complex vitamins and the intracellular messenger cyclic guanosine monophosphate (GMP) have similar effects of promoting growth, DNA and protein synthesis, the present investigation was designed to determine if the B complex vitamins' mechanism of action might involve cyclic GMP. All of the B complex vitamins increased rat cyclic GMP tissue levels. The cause of these increased cyclic GMP levels was activation of the enzyme guanylate cyclase [E.C.4.6.1.2.] which was increased significantly (P less than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
(6 reference statements)
0
11
0
1
Order By: Relevance
“…Alleviation of mechanical hyperalgesia in streptozotocin-induced diabetic rats by a mixture of vitamins B1, B6 and B12, or by vitamin B6 alone was associated with improved sensory nerve conduction velocity (Jolivalt et al, 2009), but no such change was found in rats rendered diabetic with 2,5-hexanedione and treated with vitamin B6 or B12 alone (Misumi et al, 1985). Other possible antihyperalgesic mechanisms of B vitamins include inhibition of the diacylglycerol-protein kinase C (PKC) pathway (Hammes et al, 2003;Sánchez-Ramírez et al, 2006), enhanced cGMP production by guanylylcyclase enzyme (Vesely, 1985) and increased afferent inhibitory control of nociceptive neurons at the spinal cord (Fu et al, 1998). More recently, Song et al (2009) showed that B1 vitamin treatment reduced neuronal hyperexcitability and lessen alterations of Na + currents in injured dorsal root ganglia, and proposed that such mechanisms might contribute to its thermal antihyperalgesic effect.…”
Section: Discussionmentioning
confidence: 96%
“…Alleviation of mechanical hyperalgesia in streptozotocin-induced diabetic rats by a mixture of vitamins B1, B6 and B12, or by vitamin B6 alone was associated with improved sensory nerve conduction velocity (Jolivalt et al, 2009), but no such change was found in rats rendered diabetic with 2,5-hexanedione and treated with vitamin B6 or B12 alone (Misumi et al, 1985). Other possible antihyperalgesic mechanisms of B vitamins include inhibition of the diacylglycerol-protein kinase C (PKC) pathway (Hammes et al, 2003;Sánchez-Ramírez et al, 2006), enhanced cGMP production by guanylylcyclase enzyme (Vesely, 1985) and increased afferent inhibitory control of nociceptive neurons at the spinal cord (Fu et al, 1998). More recently, Song et al (2009) showed that B1 vitamin treatment reduced neuronal hyperexcitability and lessen alterations of Na + currents in injured dorsal root ganglia, and proposed that such mechanisms might contribute to its thermal antihyperalgesic effect.…”
Section: Discussionmentioning
confidence: 96%
“…More recently, it has been shown that B vitamins-induced antinociception is partially blocked by the nitric oxide synthesis inhibitor L-NAME, but not by the inactive isomer D-NAME, suggesting that B vitamins could produce antinociception activating the nitric oxide release [Reyes-García et al, 2002]. There is evidence that either thiamine [Abaciog lu et al, 2000] or B vitamins complex activate rat guanylyl cyclase and increase intracellular cyclic GMP [Vesely, 1985]. Therefore, it is tempting to suggest that the nitric oxide-cyclic GMP pathway could have a role in the antinociceptive activity of B vitamins, as is the case for some analgesic drugs [Tonussi and Ferreira, 1994;Islas-Cadena et al, 1999;Aguirre-Bañ uelos and Granados-Soto, 1999].…”
Section: Discussionmentioning
confidence: 97%
“…However, some studies pro- vide possible explanations. First, the NO-cyclic GMP signaling pathway may be involved in B vitamin induced antiallodynic effects, as B vitamins are able to increase the activity of guanylyl cyclase and consequently the cyclic GMP tissue levels [31] . In line with these data, B vitamins may produce antinociception by activation of guanylyl cyclase in the writhing model [32] , in the formalin test [33] , and in rats with primary sensory neuron injury [34] .…”
Section: Antiallodynic Effect Of B Vitamins and Dexamethasonementioning
confidence: 99%